The Early Short Fiction of Edith Wharton $1 (BPart 1s - Wharton, Edith, 1862-1937 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Early Short Fiction of Edith Wharton $1 (BPart 1" by Edith Wharton is a collection of short stories written during the late 19th and early 20th centuries. This volume includes narratives that delve into themes of human emotion, the complexities of social relationships, and the haunting aspects of memory and loss, as showcased in stories such as "Kerfol" and "Mrs. Manstey's View." The work reflects Wharton's keen insight into the lives of the early modern American upper class and their surroundings. The opening portion of "Kerfol," the first story in the collection, introduces an unnamed narrator inspired by a friend's suggestion to visit a mysterious estate called Kerfol, steeped in history and potential ghostly tales. As the narrator explores the hauntingly beautiful landscape and eerie silence of the estate, he encounters a pack of dogs that seem to guard the property. The rich imagery emphasizes the contrast between the palpable sense of life and the ghostly feeling that pervades the house, hinting at underlying themes of longing and reflection on past events. The narrator's exploration not only serves as a physical journey but as a metaphysical one, questioning the nature of existence in the wake of past sorrow and emotional scars. (This is an automatically generated summary.)s
Kerfol -- Mrs. Manstey's view -- The bolted door -- The dilettante -- The house of the dead hand.
Release date is 1995-07-01
Produced by Judith Boss, and David Widger
Keywords: Fiction; Short stories, American